RUATAN WAYANG SAPUH LEGER BAGI ANAK YANG LAHIR WUKU WAYANG SEBAGAI TRADISI LELUHUR MASYARAKAT BALI - I Ketut Muada; Nyoman Astawan; I Made Indra Sanjaya (Widyadari, 2025)
Wayang is not only known in Bali but is supported by the majority of Indonesian people with various distinctive and high quality styles so that it is said to be one of the National cultures. A very interesting ancestral tradition, relating to wayang performances that now exist in rural communities. This is a very unique phenomenon, where according to ancestral tradition it is believed by rural communities that people born in wuku wayang should undergo a large wound ritual called Sapuh Leger. Specifically, the Sapuh Leger Wayang performance has characteristics such as; performed for people who were born in wuku wayang, the story is told by Dewa Kala who preys on children born in wuku wayang, the equipment and offerings are quite complicated according to the rules stated in the Wayang Sapuh Leger letter, then this ruatan can only be led by a master puppeteer who knows contents of the lontar dharma Pewayangan and Lontar Sapuh Leger. The problems of this research are (1) the background to the holding of the Sapuh Leger Wayang performance; (2) the function of the Sapuh Leger Wayang performance and (3) the meaning implied in the Sapuh Leger Wayang. This research includes descriptive-qualitative research formatted in a special study. The focus of the research study entitled Sapuh Leger Wayang Ritual as an Ancestral Tradition of Children Born in Wuku Wayang in Rural Communities in Bali. Data were analyzed using descriptive-qualitative methods with steps as stated by Lacey and Luff (2001) in Patilima (2005:91), which include: data transcription, data identification and reduction, data classification, data description and interpretation, data triangulation, presentation of final results